Cochrane Database of Systematic Reviews 2007
DOI: 10.1002/14651858.cd006665
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C for preventing and treating tetanus

Abstract: Cook 2007 Cook NR, Albert CM, Gaziano JM, Zaharris E, MacFadyen J, Danielson E, et al.A randomized factorial trial of vitamins C and E and beta carotene in the secondary prevention of cardiovascular events in women: results from the Women's Antioxidant Cardiovascular Study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…An early case report claimed that vitamin C was beneficial against tetanus in an unvaccinated six-year-old boy in the USA [ 128 ]. A Cochrane review identified one controlled trial in which the effect of vitamin C on tetanus patients was examined [ 129 , 130 ].…”
Section: Tetanusmentioning
confidence: 99%
“…An early case report claimed that vitamin C was beneficial against tetanus in an unvaccinated six-year-old boy in the USA [ 128 ]. A Cochrane review identified one controlled trial in which the effect of vitamin C on tetanus patients was examined [ 129 , 130 ].…”
Section: Tetanusmentioning
confidence: 99%
“…Since the publication of Roper and colleagues’ Seminar in 2007,1 there have been only four randomised controlled trials of treatment in tetanus (three in adults78–80 and one in neonates81), involving a total of 190 patients, and there have been no trials of novel therapies or regimens. In the same period, two meta-analyses have been published, with one including only one study82 and the other including three,83 two of which were published after 2007. Research into effective treatments is hampered by the settings in which most tetanus occurs—often rural and remote, and in low or low-middle income countries with few resources—and the unwillingness of funding bodies to support research into a vaccine-preventable disease.…”
Section: Managementmentioning
confidence: 99%
“…Finally, the reviewers also questioned the validity of very large survival benefits with ␤-agonists in threatened miscarriage, 22 different types of brachytherapies for stage I cervical cancer, 23 chaunxiong preparations to prevent stroke, 24 continuous vs intermittent infusion of loop diuretics in congestive heart failure, 25 and vitamin C in children with tetanus, 26 since their corresponding cumulative evidence was based on single small trials that were of very poor quality or (in the case of tetanus) apparently were not even a randomized controlled trial.…”
Section: Empirical Evaluation Of Very Large Treatment Effectsmentioning
confidence: 99%